Associations Between Movement Impairments and Function, Treatment Recommendations, and Treatment Plans for People With Femoroacetabular Impingement Syndrome. Issue 9 (23rd September 2021) - Brown-Taylor, Lindsey; Pendley, Chase; Glaws, Kathryn; Vasileff, W Kelton; Ryan, John; Harris-Hayes, Marcie; Di Stasi, Stephanie L
Abstract: Objective: The purpose of this study was to describe movement impairments for persons with femoroacetabular impingement syndrome and their association with function, treatment recommendations, and treatment plans. Methods: This report is a secondary, observational analysis of a clinical trial dataset in which participants received an interdisciplinary evaluation from a surgeon and physical therapist. The therapist documented frontal and sagittal plane movement impairments across 6 functional tasks. Associations between number of impairments in each plane and function (33-item International Hip Outcome Tool [iHOT33]) were evaluated using Pearson or Spearman correlations. Joint provider recommendations (physical therapist and surgeon) and participant-reported treatment plans were dichotomized based on the inclusion of physical therapy or not. Logistic regressions were used to examine the effects of (1) iHOT33, total movement impairments, and previous physical therapist treatment on joint provider recommendation and (2) these same variables along with joint provider recommendation on participant treatment plan; prevalence ratios and 95% CIs were reported for significant contributors. Results: Thirty-nine participants demonstrated an average iHOT33 of 35.0 (SD = 19.5) and presented with a median 5 frontal and 3 sagittal plane impairments. More frontal plane impairments were associated with worse iHOT33 scores. Twenty-seven participants received a joint provider recommendation that included physical therapy; no significant contributors to these recommendations were identified. Twenty-four of the 27 participants with a physical therapist recommendation included physical therapy in their treatment plan. Two additional participants did not receive a physical therapist recommendation but included physical therapy in their plan. Joint provider recommendation was the only significant contributor to the participant-reported plan (prevalence ratio = 7.06; 95% CI = 3.25–7.97). Conclusion: Persons with femoroacetabular impingement syndrome displayed clinically observable movement impairments that were associated with worse function. Joint provider recommendations strongly influenced participants' treatment plans to pursue physical therapy. Impact: Physical therapists contribute new information to surgical examinations regarding movement. Joint recommendations from the physical therapist and the surgeon can influence patients' decisions to pursue physical therapy.